Stateczność Otwartej Trójwarstwowej Powłoki Walcowej Dynamicznie Ściskanej - Szyc, W. (Engineering Transactions, 1972)
In the paper is solved the problem of stability of an elastic, open, sandwich cylindrical shell subject to the action of compressive forces uniformly distributed along the edges and variable in time. Basing on the broken line hypothesis and the Hamilton principle, the equations of motion of the shell element are derived. Introduction of the stress and displacement functions yields the system of three equations which is then approximately solved by the Bubnov-Galerkin method. Under the assumption of linearly increasing load in time, a nonlinear differential equation is derived combining the deflection parameters and time. Numerical examples are also presented, their results serving for the qualitative analysis of the influence of individual physical and geometric parameters of the shell on the buckling process.